Francisco J. Medina-Albaladejo, José Miguel Martínez-Carrión and Salvador Calatayud (eds.) (2023). Inequality and Nutritional Transition in Economic History. Spain in the 19th-21st centuries - Salvatore, Ricardo (América Latina en la Historia Económica, 2024)
Sin resumen